Impact of Tera Exercise on Musculoskeletal Health in Older Adults - Shinta Silaswati; Dwi Juliani Pramestika; Tri Lestari Handayani (CV Media Inti Teknologi, 2026)
Background of study: The aging process in older adults is accompanied by musculoskeletal changes that frequently manifest as joint pain, impairing daily functioning, independence, and overall quality of life. Non-pharmacological interventions are increasingly explored, with tera exercise—a light exercise emphasizing stretching, joint mobility, flexibility, circulation, and relaxation—emerging as a promising approach.Aim : This study aimed to evaluate the effectiveness of tera exercise in reducing joint pain among elderly residents of a private nursing home in Jakarta, thereby providing empirical evidence for its role as a non-pharmacological intervention to improve musculoskeletal health and quality of life.Methods: A quasi-experimental design with a one-group pretest–posttest approach was employed. Using purposive sampling, 20 respondents were recruited. Joint pain levels were measured using the Numeric Rating Scale (NRS) before and after a two-week tera exercise program conducted three times per week. Data were analyzed using the Wilcoxon Signed Rank Test.Result: Prior to the intervention, 10 respondents (50%) reported mild to moderate pain, while 10 respondents (50%) experienced severe to very severe pain. After the intervention, 17 respondents (85%) reported mild to moderate pain, and only 3 respondents (15%) remained in the severe to very severe category. Statistical analysis yielded a p-value < 0.05 and a Z-score of -2.646, indicating a significant reduction in joint pain.Conclusion: Tera exercise is an effective non-pharmacological strategy for alleviating joint discomfort and improving musculoskeletal health among older adults in nursing home settings. However, limitations include the small sample size and absence of a control group. Future studies should employ larger samples, randomized controlled designs, longer observation periods, and examine additional factors such as physical activity, psychological status, and pharmacological therapies.